Komitas and the Problems of Armenian Music Folkloristics - Pahlevanyan, Alina (Կոմիտասի թանգարան-ին-տ. հրատ.)
Collecting several thousands of folk songs and tunes, Komitas studied and classified them into genres. The next step was searching for the polyphony convenient for the Armenian music structure. This article attempts to explain why Komitas was the founder of the national school of music composition, as commonly accepted in Armenian musicology. The following problems propounded by Komitas are addressed to:  What is the oral tradition in Armenian folk music? What role does permanent improvisation have inside an oral tradition?  What is the advantage of music notation? What losses can be registered in the case of notation? How do written and oral traditions relate to each other?  Revealing the “music dialects” typical for each region.  The problem of the existence or the absence of an author in folk song creation.  The viability of the songs, their lifespan. Which songs live longer and which do not?  Identifying the musical phrases typical for the songs and finding the formulaic expressions. To what extent may improvisation exist within formulaic constructions?  The stationary approach in song collection work.  The rhythm in Armenian folk songs. Obviously, Komitas surpassed his time–period preordaining several problems of folkloristics. Komitas actually proposed pathways for further development of ethnomusicology. Հավաքելով հազարավոր ժողովրդական երգեր և մեղեդիներ՝ Կոմիտասը դրանք ուսումնասիրել է և դասակարգել ըստ ժանրերի: Հաջորդ քայլը եղել է հայ երաժշտության կառուցվածքին համապատասխան բազմաձայնության որոնումը: Սույն հոդվածը փորձ է բացատրելու, թե ինչու էր Կոմիտասը հայ ազգային կոմպոզիտորական դպրոցի հիմնադիրը, ինչպես ընդունված է համարել հայ երաժշտագիտության մեջ: Քննվում են Կոմիտասի առաջադրած հետևյալ խնդիրները:  Ո՞րն է հայ ավանդական երաժշտության բանավոր էությունը: Ո՞րն է իմպրովիզացիայի դերը բանավոր ավանդույթի ներսում:  Ի՞նչ դեր ունի նոտագրությունը երաժշտության մեջ: Ի՞նչ կորուստներ են լինում նոտագրության դեպքում: Ինչպե՞ս են փոխհարաբերվում գրավոր և բանավոր ավանդույթները:  Յուրաքանչյուր տարածաշրջանին բնորոշ երաժշտական բարբառների բացահայտումը:  Ժողովրդական երաժշտական ստեղծագործության մեջ հեղինակի գոյության կամ բացակայության խնդիրը:  Երգերի կենսունակությունը, նրանց կյանքի տևողությունը: Ո՞ր երգերն են ապրում ավելի երկար, և որո՞նք կարճ կյանք ունեն:  Երգերին հատուկ երաժշտական ֆրազների բնորոշումը և բանաձևային արտահայտությունների դուրս բերումը: Ի՞նչ չափով կարող է իմպրովիզացիան գոյություն ունենալ բանաձևային մտածողության մեջ:  Բանահավաքչության մեջ երգի ստացիոնար գրառման մոտեցումը:  Ռիթմը հայ ժողովրդական երգի մեջ:Ակնհայտորեն Կոմիտասը գերազանցել է իր ժամանակը և կանխորոշել է ֆոլկլորագիտության մի շարք հիմնախնդիրներ: Փաստորեն, նա ուղիներ է առաջադրել ֆոլկլորագիտության հետագա զարգացման համար:
Keywords: Museums; Komitas Vardapet; Folk Music